Antibacterial Activity Test of Lerak Fruit Extract (Sapindus rarak DC.) Against the Growth of the Bacterist Streptococcus Mutans - Risnawati Risnawati; Kartika Sari (International Journal Labs, 2026)
Lerak (Sapindus rarak DC.) is a plant native to Southeast Asia that grows well in Indonesia, especially in Sumatra and Java. Lerak is traditionally used as a laundry detergent, facial soap, insect repellent, and fungus repellent. Lerak contains phytochemical compounds that function as antibacterials. This study aims to test the antibacterial activity of lerak fruit extract against Streptococcus mutans bacteria, which cause dental caries. The method in this study involves preparing lerak fruit extract by maceration using 70% ethanol solvent and conducting an inhibition zone test using the diffusion method. Based on the test results, the lerak fruit extract is positive for alkaloids, flavonoids, tannins, saponins, and terpenoids. The results also showed that increasing the concentration of lerak fruit extract produced a wider inhibition zone. The average inhibition zones at concentrations of 25%, 50%, and 100% were 8.83 ± 0.958 mm, 11.78 ± 3.081 mm, and 12.14 ± 0.918 mm, respectively. The novelty of this research lies in the comprehensive evaluation of lerak fruit extract's antibacterial potency against S. mutans using systematic concentration gradients, which has not been extensively documented in previous literature. This study provides practical implications, as lerak fruit extract demonstrates potential as an alternative natural antibacterial agent for oral health applications, offering a safer option with fewer side effects compared to synthetic chemical compounds. However, this study is limited to in vitro testing against a single bacterial strain, and further research is needed to evaluate its efficacy in clinical settings and against polymicrobial oral biofilms.